Substitutent effects in the periphery of 2,9-bisaryl-tetraazaperopyrene dyes - Martens-Kruck, Susanne; Riehm, Till; Geib, Sonja; Wadepohl, Hubert; Gade, Lutz H. (The journal of organic chemistry, 2011)
A series of 2,9-bisaryl-1,3,8,10-tetraazaperopyrene (TAPP) derivatives has been synthesized by reacting 4,9-diamino-3,10-perylenequinone diimine with a large excess of the corresponding benzoyl chloride in refluxing nitrobenzene. Among all derivatives only ortho-substituted phenyl congeners were sufficiently soluble for studying solutions of defined concentration in organic solvents. The molecular structures of the crystallized compounds, determined by X-ray diffraction of four derivatives, are determined by the planar tetraazaperopyrene core and the interplanar angle of the phenyl rings, which depends on the size of the ortho substituent (40−70°). The intermolecular packing pattern of all compounds is characterized by parallel stacks of molecules with the substituted phenyl rings rotated out of the peropyrene plane to reduce the steric repulsion. Crystals of a TAPP derivative suitable for X-ray diffraction were grown from trifluoroacetic acid (TFA) for the first time, establishing a 2-fold protonated species. The ground-state geometries of the TAPP derivatives were calculated by DFT [B3PW91/6-31g(d,p)] and the lowest unoccupied molecular orbital (LUMO) energies of derivatives possessing electron-withdrawing groups were decreased, as were the computed electron affinities. The results of the modeling study were confirmed experimentally by cyclic voltammetry to evaluate the substituent effects on the highest occupied molecular orbital (HOMO) and the LUMO of the peropyrene core. The UV−vis absorption spectra of all compounds recorded in trifluoroacetic acid are almost superimposable and display a characteristic visible absorption band between 460 and 490 nm (log ε = 4.64−5.01) with a strong vibrational progression of 1173−1475 cm−1. Their fluorescence spectra are characterized by bands between 490 and 530 nm that are the mirror images of the absorption spectra (Stokes shifts of 10−50 nm). The luminescence quantum yields range from <0.01 to 0.30, thereby indicating a quenching effect for some substitution patterns.